British dystopian novel and its vision of threats to the individual - Stehnová, Pavla (Univerzita Pardubice, 2009)
The aim of this thesis is to find out how the characters of the British dystopian novels (Orwell's Nineteen Eighty-Four, Huxley's Brave New World and Burgess' A Clockwork Orange) are suppressed by various authorities. The paper considers the revolt of the individual, conflict with the government and nature of fear. The study also describes the main features of dystopian literature and compares them with classical utopian visions of More's Utopia. The main part of the thesis includes the analysis and comparison of the above mentioned dystopian novels.
Britský antiutopický román: vztah jedince a autority
Keywords: antiutopie; utopie; autorita; jedinec; manipulace; revolta; dystopia; utopia; authority; individual; manipulation; revolt